Leiomyosarcoma in the rectum in the newborn period (a case report) - Hiçsönmez, Akgün; Kalayoğlu, Münci (The Turkish Journal of Pediatrics, 1975)
Malignant tumors of the rectum are uncommon in the newborn period. This report presents leiomyosarcoma of the rectum in a newborn which we believe to be the first case in the medical literature. Six months after the partial resection of the tumor, resected material which was left in the first intervention showed no tumor cells.